A rapid landscape review of postpartum anaemia measurement: challenges and opportunities - Jennifer Yourkavitch; Hiromi Obara; Gulnoza Usmanova; Katherine E. A. Semrau; Ann-Beth Moller; Maria Nieves Garcia-Casal; Jahnavi Daru (BMC, 2023)
Abstract Background Anaemia is a reduction in haemoglobin concentration below a threshold, resulting from various factors including severe blood loss during and after childbirth. Symptoms of anaemia include fatigue and weakness, among others, affecting health and quality of life. Anaemic pregnant women have an increased risk of premature delivery, a low-birthweight infant, and postpartum depression. They are also more likely to have anaemia in the postpartum period which can lead to an ongoing condition and affect subsequent pregnancies. In 2019 nearly 37% of pregnant women globally had anaemia, and estimates suggest that 50-80% of postpartum women in low- and middle-income countries have anaemia, but currently there is no standard measurement or classification for postpartum anaemia. Methods A rapid landscape review was conducted to identify and characterize postpartum anaemia measurement searching references within three published systematic reviews of anaemia, including studies published between 2012 and 2021. We then conducted a new search for relevant literature from February 2021 to April 2022 in EMBASE and MEDLINE using a similar search strategy as used in the published reviews. Results In total, we identified 53 relevant studies. The timing of haemoglobin measurement ranged from within the immediate postpartum period to over 6 weeks. The thresholds used to diagnose anaemia in postpartum women varied considerably, with < 120, < 110, < 100 and < 80 g/L the most frequently reported. Other laboratory results frequently reported included ferritin and transferrin receptor. Clinical outcomes reported in 32 out of 53 studies included postpartum depression, quality of life, and fatigue. Haemoglobin measurements were performed in a laboratory, although it is unclear from the studies if venous samples and automatic analysers were used in all cases. Conclusions This review demonstrates the need for improving postpartum anaemia measurement given the variability observed in published measures. With the high prevalence of anaemia, the relatively simple treatment for non-severe cases of iron deficiency anaemia, and its importance to public health with multi-generational effects, it is crucial to develop common measures for women in the postpartum period and promote rapid uptake and reporting.